An economic analysis of gas pipeline trade cooperation in the GCC - Williams-Rioux, Bertrand (2021)
Natural gas plays an important role in the global energy system. Thus, optimizing trade in natural gas is a key concern for many countries. This study investigates the value of expanding the Gulf Cooperation Council's (GCC) natural gas grid. We consider the documented successes and failures of the regional gas trade in Europe and Asia and weigh them against a GCC case study. The case study uses a partial equilibrium model of energy production, trade and demand calibrated to 2018 conditions to assess regional pipeline gas trade opportunities. The model incorporates parameters that are relevant to energy policy issues, including fuel allocation and energy price reforms. We also incorporate the regional liquified natural gas (LNG) trade strategy of Qatar, a regional and global leader in LNG production and exports. We find that pipeline gas trade cooperation in the GCC can contribute up to $3.1 billion to the regional economy by reducing transportation costs. More accessible gas offers a substitute for liquid fuel consumption and can offset the opportunity costs of using domestic oil to meet domestic energy demands. We also investigate the influence of an integrated gas market and price reforms on the power trade along the GCC interconnector.